Brain correlates of short-term habituation to repetitive electrical noxious stimulation - Nickel, Franziska; Ott, Sabine; Möhringer, Susanne; Saake, Marc; Dörfler, Arnd; Seifert, Frank; Maihöfner, Christian (European Journal of Pain, 2014)
Habituation to repetitive noxious stimuli is a well-known phenomenon. We investigated brain correlates of habituation to pain in a transdermal electrical pain model using functional magnetic resonance imaging (fMRI).Electrical painful stimulation with 1 Hz was applied to the volar forearm of 48 healthy subjects for 45 min. Before and after conditioning stimulation, psychophysical testing and fMRI were performed. During fMRI sessions, the subjects underwent blockwise painful electrical stimulation with a fixed percept-adapted current intensity. After fMRI 1 and fMRI 2 subjects rated the individual pain intensity of the electrical stimulus.Substantial habituation occurred during conditioning electrical stimulation. Accordingly, areas typically involved in pain processing showed decreased activity after conditioning stimulation. The blood oxygen level-dependent signal of the subgenual anterior cingulate gyrus, the superior parietal lobule and the supplemental motor area correlated positively with habituation. In contrast, activity in the periaqueductal grey, thalamus and insula correlated negatively. The results of the correlation analyses did not survive correction for multiple comparisons.With this study, we identified central components associated with habituation to repetitive painful stimuli. The results suggest that an increase in tonic inhibitory activity in cortical pain processing areas is a major mechanism contributing to habituation to phasic noxious stimuli. Moreover, areas involved in descending pain modulation were differentially modulated. This may hint at a simultaneous activation of facilitating and inhibiting nociceptive systems that are both altered in the transdermal electrical pain model.
EVALuna2:14468

C9ORF72-ALS: P62- and ubiquitin-aggregation pathology in skeletal muscle - Türk, Matthias; Haaker, Gerrit; Winter, Lilli; Just, Walter; Nickel, Franziska; Linker, Ralf; Chevessier, Frederic; Schröder, Rolf (Muscle & Nerve, 2014)
EVALuna2:7243

Diagnosis of cognitive decline and dementia in rural areas - A scoping review - Barth, Janina; Nickel, Franziska; Kolominsky-Rabas, Peter (International Journal of Geriatric Psychiatry, 2018)
OBJECTIVES: Due to the demographic change, the global prevalence of dementia will continually rise. Barriers to diagnosis and care are still high. But timely diagnosis is associated with valuable benefits and can promote timely and optimal management. Receiving an early diagnosis is especially in rural areas a problem due to the limited access to assessments. Therefore, the aim of our scoping review is to investigate different interventions targeted at rural living elderly to screen and diagnose cognitive decline and dementia. METHODS: A scoping review was conducted in line with the framework of Arksey and O'Malley. The following databases were systematically searched: PubMed, PsycINFO, Cochrane Library, and ScienceDirect. The interventions were categorized in four main categories (interventions for general practitioners/institutions; online/mobile offers; telehealth applications; telephone-based screenings). RESULTS: Thirty studies were included. The four categories show different scopes of application. Telehealth applications show that it is feasible and valid to diagnose dementia via videoconference. Assessments described in three other categories show that remotely used tools are appropriate to screen for mild cognitive impairment or cognitive decline, but are not valid to establish a dementia diagnosis. CONCLUSIONS: Telehealth applications can appropriately be used to diagnose dementia. However, most of the studies included only small sample sizes and did not test the applications explicitly in rural or remote populations. Therefore, studies taking these limitations into account are needed. On top, only two RCTs are included in this review indicating that more high quality studies in this field are needed.
EVALuna2:33836

Effects of Different Anesthetics on Pain Processing in an Experimental Human Pain Model - Nickel, Franziska; Ott, Stephan; Möhringer, Susanne; Münster, Tino; Rieß, Simon; Filitz, Joerg; Koppert, Wolfgang; Maihoefner, Christian (Pain Practice, 2016)
After surgical procedures, anesthesia itself may affect pain perception. Particularly, there is increasing evidence that opioids not only have analgesic effects but also provoke pronociceptive changes, that is, opioid-induced hyperalgesia. We investigated the effect of different anesthetic regimens on pain processing in volunteers using a transdermal electrical pain model. In this model, stimulation of epidermal nerve fibers representing mainly peptidergic C-nociceptors leads to secondary hyperalgesia and habituation to the stimulus.Forty-eight healthy volunteers underwent conditioning noxious stimulation (CS) over 5 days. On day 2, the volunteers were randomized into 4 groups: control group (no anesthesia) and 3 groups receiving anesthesia before CS in anesthetic doses: propofol (P), propofol/remifentanil (PR), and propofol/remifentanil/S-ketamine (PRK). Quantitative sensory testing was performed on days 1 through 5 and on day 22.In every group, CS was associated with short- and long-term habituation to the electrical stimulus. Repetitive CS resulted in unmodified short-term sensitization with stable areas of hyperalgesia. Although the PR group showed a trend toward increased areas of hyperalgesia on day 2, no significant differences were detectable between the groups. In contrast, anesthesia resulted in decreased intensity of the electrically evoked pain on day 2. Finally, the mechanical pain threshold before CS on day 5 was increased in all groups and remained elevated 3 weeks after the first CS, consistent with a long-term antinociceptive effect after CS.The results suggest a short-term analgesic effect of general anesthesia. Furthermore, the conditioning stimulation over several days induced differential modulation of pro- and antinociceptive systems.
EVALuna2:16707

Einflussfaktoren auf die Pflegebelastung der Angehörigen von Menschen mit Demenz: der Bayerische Demenz Survey (BayDem) - Dietzel, Nikolas; Karrer, Linda; Wolff, Franziska; Kratzer, André; Hess, Manuela; Grässel, Elmar; Kolominsky-Rabas, Peter (Gesundheitswesen, 2020)
Background Dementia is an age-specific disease with increasing care needs over the course of the disease. Care is predominantly conducted by caregivers. Caregiver burden is a core criterion for the evaluation of the care situation. The aims of this examination are to identify predictors of caregiver burden and to analyze the course of the caregiver burden over a 12 months period. Methods The Bavarian Dementia Survey (BayDem) is a supra-regional, longitudinal study carried out at 3 different sites in Bavaria, Germany. Participants were people with dementia (pwd) as defined by ICD-10 and their informal caregivers. Data was collected by standardized face-to-face interviews in cooperation with local actors. For statistical analysis, a multiple regression as well as a mixed ANOVA (Analysis of Variance) and repeated measures ANOVAs were used. Results In this analysis, 295 pwd and 276 caregivers were studied. Key factors influencing caregiver burden were gender of the pwd, behavioral and psychological symptoms and a decline of everyday functioning of the pwd as well as gender of the informal caregivers, their relation to the pwd and if they live at the same household as the pwd. Analysis showed a significant main effect of time over the course of the caregiver burden. Conclusion A permanent high caregiver burden can cause health problems for the caregivers. However, caregivers can be supported according to the specific factors of the caregiver burden. One approach in order to support caregivers could be a combination of pharmacological and non-pharmacological interventions for the treatment of disease-specific symptoms and an empowerment as well as the provision of support services for the caregivers. Furthermore, tailored services for specific target groups can be meaningful.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Burden Scale for Family Caregivers (BSFC-s); caregiver burden; course; dementia; informal caregivers; predictors

Health economic evaluations of non-pharmacological interventions for persons with dementia and their informal caregivers: a systematic review - Nickel, Franziska; Barth, Janina; Kolominsky-Rabas, Peter (BMC Geriatrics, 2018)
BACKGROUND: This systematic review aims to review the literature on trial-based economic evaluations of non-pharmacological interventions directly targeted at persons with dementia as well as persons with mild cognitive impairment and their respective caregivers. METHODS: A systematic literature research was conducted for the timeframe from 2010 to 2016 in the following databases: Centre for Reviews and Dissemination, EconLit, Embase, Cochrane Library, PsycINFO and PubMed. Study quality was assessed according to the Drummond criteria. RESULTS: In total sixteen publications were identified. Health economic evaluations indicated the cost-effectiveness of physical exercise interventions and occupational therapy. There was also evidence to suggest that psychological and behavioral therapies are cost-effective. Health economic studies investigating psychosocial interventions mainly targeted towards informal caregivers showed inconsistent results. CONCLUSIONS: Due to the increasing prevalence of dementia non-pharmacological interventions and their health economic impact are of increasing importance for health care decision-makers and HTA agencies.
EVALuna2:33835

Longer-term effects of intravenous immunoglobulin treatment in chronic inflammatory demyelinating polyneuropathy: Who benefits? - Terhoeven, Pauline; Seybold, Julia; Utz, Katrin; Nickel, Franziska; Lee, De-Hyung; Linker, Ralf (Journal of the Neurological Sciences, 2020)
Intravenous immunoglobulins (IVIg) represent an established cornerstone for the immunotherapy of chronic inflammatory demyelinating polyneuropathy (CIDP). Efficacy of IVIg for CIDP was proven in a large phase III trial. Yet, data on longer-term efficacy and effects in distinct subgroups are scarce. Our trial investigates the long-term efficacy of IVIg treatment in CIDP patients. In this observational real-world study, we retrospectively analyzed 49 CIDP patients receiving continuous IVIg treatment with a mean initial dosage of 87 g (1 g/kg body weight) every 4 weeks over a mean time of 45 months between 2010 and 2018. INCAT-Scores before the start of treatment and at the end of the observation period were compared. Over the observation period, IVIg treatment led to a median improvement of one INCAT score point. Subgroup analyses revealed a more pronounced improvement of INCAT scores in female CIDP patients, individuals with relapsing disease courses, patients with more pronounced motor impairment (higher initial INCAT scores) and in the cohort without need for concomitant other immunotherapies. These data argue for sustained beneficial effects of longer-term immunotherapy with IVIg in CIDP, particularly in females and relapsing disease forms with higher disease activity.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Chronic inflammatory demyelinating polyneuropathy; Immunotherapy; Intravenous immunoglobulins; Long-term effect; Polyneuritis

Neuromodulation of Electrically Induced Hyperalgesia in the Trigeminocervical System - Reindl, Caroline; Seifert, Frank; Nickel, Franziska; Maihoefner, Christian (Pain Practice, 2016)
Trigeminal and cervical afferents converge on neurons of the trigeminocervical complex and may significantly alter the function of these neurons. This interaction may have implications for the pathophysiology and treatment of primary headache disorders. Therefore, the aim of this work was to study pain modulatory mechanisms within the trigeminocervical complex.We used an electrical pain model challenging pro- and antinociceptive systems in 19 healthy volunteers.Transcutaneous supraorbital noxious electrical low-frequency stimulation (0.5 Hz), known to induce both hyperalgesia due to central sensitization (as a marker of pain facilitation) and habituation (as a marker of pain inhibition), was combined with different noxious stimulation paradigms applied to the innervation territory of upper cervical afferents. We investigated the effects of concurrent stimulation in the cervical/extratrigeminal system on habituation profiles, hyperalgesic area, pain, and detection thresholds in the trigeminal system.It was previously shown that conditioning 20-Hz noxious electrical stimuli may provoke centrally mediated sensory decline that possesses heterotopic antihyperalgesic properties. Occipital and forearm costimulation at a frequency of 20 Hz had no significant modulating effect on supraorbital pain adaptation, hyperalgesic area, or pain perception. Effects for trigeminal stimulation were independent of occipital stimulus intensity. Furthermore, for single occipital stimulation at 0.5 and 20 Hz, no somatosensory changes could be demonstrated within the trigeminal system.Trigeminal nociception stayed unchanged despite of occipital costimulation.
EVALuna2:22473

Real world application of ocrelizumab in multiple sclerosis: Single-center experience of 128 patients - Prockl, Victoria; Nickel, Franziska; Utz, Kathrin S.; Fröhlich, Kilian; Engelhorn, Tobias; Hilz, Max-Josef; Lee, De-Hyung; Linker, Ralf; Huhn, Konstantin (Journal of the Neurological Sciences, 2020)
Background: Pivotal trials showed good clinical efficiency of the monoclonal antibody ocrelizumab while being well tolerated and manageable in multiple sclerosis (MS). However, data on adverse events in everyday practice are scarce. Hence, our study aims at investigating short-term tolerability of ocrelizumab in a “real-world” setting. Methods: In this retrospective cohort study, data of 128 (86 relapsing-remitting, 42 progressive) MS patients at initiation of ocrelizumab were analyzed at the MS center of the University of Erlangen, Germany. Additionally, follow-up data of 68 patients at 6-months retreatment were analyzed. Structured phone interviews were applied after ocrelizumab initiation to report undocumented side effects. Results: Patients predominantly switched from monoclonal antibodies (46%), orals (20%), injectables (10%), steroids or immunosuppressants (each 8%), with a mean interval of 9.0 months after the last application of the previous immunotherapy. Applying a combined premedication with steroids, antihistamines and antipyretics for >90% of patients, ocrelizumab treatment was well tolerated and mainly comprised mild (n = 59/128 at initiation, n = 5/68 at 6 months retreatment) and rarely moderate (n = 7/128 at initiation, n = 2/68 at 6 months) side effects. Predominantly mild infusion related reactions (IRR) were reported with a declining percentage over the follow-up applications. Infections occurred rarely. No severe side effects were observed. Secondary, treatment appeared efficient when looking at clinical surrogates of stable disease. Discussion: Our study delineates good short-term tolerability of ocrelizumab in a miscellaneous “real-world” MS cohort. Additional studies are warranted to confirm these beneficial findings and to reveal safety concerns in the longer-term follow-up.
CRIS-Team Scopus Importer:2020-06-26
Keywords: B-cell depletion; CD 20; Immunomodulatory treatment; Monoclonal antibody; Multiple sclerosis; Ocrelizumab; Side effects

SERIO - Side Effect Registry Immuno-Oncology Side Effect Registry for rare, severe and complex Side Effects of Immunotherapy - Kramer, Rafaela; Mentzer, D.; Erdmann, M.; Knauss, S.; Broeckelmann, P. J.; Hassel, J. C.; Ugurel, S.; Pavel, Marianne Ellen; Nickel, Franziska; Landendinger, M.; Fuchs, Friederike; Meidenbauer, Norbert; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Symptombelastung, Inanspruchnahme des Gesundheitssystems und Todesumstände von Menschen mit Demenz in der letzten Lebensphase: der Bayerische Demenz Survey (BayDem) - Kratzer, André; Karrer, Linda; Dietzel, Nikolas; Wolff, Franziska; Hess, Manuela; Kolominsky-Rabas, Peter; Grässel, Elmar (Gesundheitswesen, 2020)
Background Dementia is usually a life-limiting disease. However, evidence-based guidelines for palliative care for people with dementia (PwD) are currently lacking. One reason for this is the dearth of reliable empirical data on PwD at the end of life. The aim of this study is to describe the symptom burden, causes of death, places of death and the use of various health services for PwD at the end of life. Methods The Bavarian Dementia Survey (BayDem) was a multi-center, longitudinal study at 3 different sites in Bavaria, Germany (Dachau, Kronach, Erlangen). Participants were PwD defined by ICD-10 and their informal caregivers. Data were collected in standardized face-to-face interviews in cooperation with local actors. In order to obtain comparable groups, deceased and non-deceased PwD were matched using 1:1 propensity score matching. For the statistical analyses, McNemar tests as well as paired t-tests were used. Results In this analysis, 58 deceased and 58 non-deceased PwD were studied (n=116). In most cases, PwD died at home (36.2%), in hospital (25.9%) or in a nursing home (19.0%), but no one in palliative care. The most common causes of death were respiratory (13.8%) and cardiovascular complications (12.1%) as well as stroke (12.1%). PwD at the end of life showed more pronounced physical comorbidities than the other PwD (Charlson-Index: M=2.75 vs. M=1.80; p=0.030, Cohen's d=0.425) and were therefore admitted to hospital (46.6 vs. 12.1%, p<0.001, OR=6.250) or emergency departments (22.4 vs. 3.4%, p=0.007, OR=6.500) more frequently. Behavioral and psychological symptoms were very pronounced (NPI Score: M=31.67 vs. M=24.77, p=0.118, Cohen's d=0.303). Nevertheless, the utilization of outpatient health services was low. Conclusion The results underline the need to develop evidence-based guidelines to provide palliative care specifically adapted to the needs of PwD at the end of life. In this context, the high incidence of behavioral and psychological symptoms should be taken into account, as should the high incidence of physical comorbidities. Considering the frequent hospital admissions, special attention should also be paid to the development of recommendations for the inpatient sector (acute hospital and palliative care unit).
CRIS-Team Scopus Importer:2020-02-04
Keywords: Death; Dementia; End of life; Palliative care; Symtom burden; Utilization

Voxel-wise lesion mapping of self-reported urinary incontinence in multiple sclerosis - Fröhlich, Katharina; Wang, Ruihao; Bobinger, Tobias; Schmidt, Manuel; Dörfler, Arnd; Nickel, Franziska; Hilz, Max-Josef; Lee, De-Hyung; Linker, Ralf A.; Seifert, Frank; Winder, Klemens (Neurourology and Urodynamics, 2019)
Aims Besides spinal lesions, urinary incontinence may be attributed to particular cerebral lesion sites in multiple sclerosis (MS) patients. We intended to determine the contribution of suprapontine lesions to urinary incontinence in MS using a voxel-wise lesion analysis. Methods In this retrospective study, we sought MS patients with documented urinary incontinence in a local database. We established a control group of MS-patients without documented urinary incontinence matched for gender, age, and disease severity. Patients with urinary incontinence due to local diseases of the urinary tract were excluded. The MS lesions were analyzed on T2-weighted magnetic resonance imaging scans (1.5 or 3T). After manual delineation and transformation into stereotaxic space, we determined the lesion overlap and compared the presence or absence of urinary incontinence voxel-wise between patients with and without lesions in a given voxel performing the Liebermeister test with 4000 permutations. Results A total of 56 patients with urinary incontinence and MS fulfilled the criteria and were included. The analysis yielded associations between urinary incontinence and MS in the frontal white matter, temporo-occipital, and parahippocampal regions. Conclusions Our voxel-wise analysis indicated associations between self-reported urinary incontinence and lesions in the left frontal white matter and right parahippocampal region. Thus, our data suggest that dysfunction of supraspinal bladder control due to cerebral lesions may contribute to the pathophysiology of urinary incontinence in MS.
CRIS-Team WoS Importer:2019-11-12

Wenn es nicht mehr alleine geht – Inanspruchnahme ambulanter Unterstützungsangebote von Menschen mit Demenz: der Bayerische Demenz Survey (BayDem) - Karrer, Linda; Dietzel, Nikolas; Wolff, Franziska; Kratzer, André; Hess, Manuela; Grässel, Elmar; Kolominsky-Rabas, Peter (Gesundheitswesen, 2020)
Background The increasing prevalence of dementia raises challenges concerning the care of people with dementia (pwd). The care of pwd is mainly conducted by informal caregivers who are faced with several burdens; however, use of care services is generally low. The aim of this study was to identify predictors of the use of outpatient care services. Methods The Bavarian Dementia Survey (BayDem) is a multi-centre, longitudinal study that was conducted at 3 different sites in Bavaria, Germany. Participants were people with dementia (pwd) (according to ICD-10) and their informal caregivers. Data were collected by standardised face-to-face interviews using well-designed instruments in cooperation with local partners. Logistic regression analysis was carried out in order to identify predictors of the use of outpatient care services. Results In total, 364 pwd and 339 informal caregivers were included at the beginning of the study BayDem. The use of supportive care services was generally low. One-third of all participants used outpatient care services. In the logistic regression analysis, the following significant predictors for the use of outpatient care services 6 months after baseline were identified: severity of cognitive impairment of the pwd; use of outpatient care at the beginning of the study. Conclusion The low use of outpatient care services is a well-known paradoxical phenomenon. Such services can help give relief to informal caregivers. In order to enhance the use of supportive outpatient care services, there should be more focus on innovative health service delivery models with a low access threshold barrier. Besides more public campaigns, more guidance for existing offers is needed.
CRIS-Team Scopus Importer:2020-02-04
Keywords: informal caregivers; outpatient care; People with dementia; Resource Utilization in Dementia (RUD); use of care services

Zeitgerechte Diagnosestellung bei Menschen mit Demenz: der Bayerische Demenz Survey (BayDem) - Wolff, Franziska; Dietzel, Nikolas; Karrer, Linda; Kratzer, André; Hess, Manuela; Grässel, Elmar; Kolominsky-Rabas, Peter (Gesundheitswesen, 2020)
Background In many cases, people with dementia (PWD) receive their first diagnosis at an advanced stage of the disease. A timely diagnosis, however, is crucial for the utilization of therapies and support services for PWD and their caregivers. So far, only a few international studies have analysed predictors of the time lapse between the first perceived symptoms and diagnosis. The aim of this study was to assess the time span from the first symptoms of dementia until the first dementia diagnosis and to identify predictors of a timely diagnosis. Methods The Bavarian Dementia Survey (BayDem) is a multi-centre, longitudinal study at 3 different sites in Bavaria, Germany. Participants were PWD as defined by ICD-10 and their informal caregivers. Data was collected by standardized face-to-face interviews in cooperation with local actors. For the analysis of potential sociodemographic predictors of a timely diagnosis within 9 months after the perception of the first symptoms, binary logistic regressions were used. Results The median length from the perception of the first symptoms until diagnosis was 16 months. Predictors of a timely diagnosis for male PWD were age at the time of the first perceived symptoms and education. There was no association between a timely diagnosis and the place of residence or living situation of the PWD. Conclusions Diagnosis of dementia is often made with a huge delay. Therefore, it is necessary to enhance structured access routes to a timely diagnosis in primary care.
CRIS-Team Scopus Importer:2020-02-04
Keywords: dementia; diagnostic delay; time to diagnosis; timely diagnosis